Clinical, Neuroimmunologic, and CSF Investigations in First Episode Psychosis. (6th July 2021) - Guasp, Mar; Giné-Servén, Eloi; Maudes, Estibaliz; Rosa-Justicia, Mireia; Martínez-Hernández, Eugenia; Boix-Quintana, Ester; Bioque, Miquel; Casado, Virginia; Módena-Ouarzi, Yasmina; Guanyabens, Nicolau; Muriana, Desiree; Sugranyes, Gisela; et al.
Abstract : Objectives: To report the neuropsychiatric features and frequency of NMDA receptor (NMDAR) and other neuronal immunoglobulin G antibodies in patients with first episode psychosis (FEP) and to assess the performance of reported warning signs and criteria for autoimmune psychosis (AP). Methods: This was a prospective observational study of patients with FEP assessed for neuropsychiatric symptoms, serum and CSF neuronal antibodies (brain immunohistochemistry, cell-based assays, live neurons), and warning signs and criteria of AP. Previous autoimmune FEP series were reviewed. Results: One hundred five patients were included; their median age was 30 (range 14–75) years, and 44 (42%) were female. None had neuronal antibodies. Two of 105 (2%) had CSF pleocytosis, 4 of 100 (4%) had brain MRI abnormalities, and 3 of 73 (4%) EEG alterations. Thirty-four (32%) and 39 (37%) patients fulfilled 2 sets of warning signs of AP, and 21 (20%) fulfilled criteria of possible or probable AP, yet none developed AP. The cause of FEP was psychiatric in 101 (96%) and nonpsychiatric in 4 (4%). During this study, 3 patients with psychosis caused by anti-NMDAR encephalitis were transferred to our center; 2 did not meet criteria for possible AP. Of 1, 159 reported patients with FEP, only 7 (1%) had CSF studies; 36 (3%) had serum NMDAR antibodies (without definite diagnosis of AP), and 4 had CSF NMDAR antibodies (3 classic anti-NMDAR encephalitis and 1 with isolated psychiatric features). Conclusions: NMDAR antibodies were not found in patients with FEP unless they had anti-NMDAR encephalitis. Warning signs and criteria for AP have limited utility when neurologic symptoms are absent or paraclinical tests are normal. A diagnostic algorithm for autoimmune FEP is provided.